Vulnerability of Selected Soils in the Different Rainfall Areas to Degradation and Excessive Leaching after Winery Wastewater Application - Mulidzi, A.R.; Clarke, C.E.; Myburgh, P.A. (South African Journal of Enology and Viticulture, 2020)
A pot trial was conducted to assess the effect of simulated rainfall on six soils with different textures, irrigated with winery wastewater diluted to a chemical oxygen demand (COD) level of 3000 mg/L over one simulated irrigation season. Thereafter, simulated winter rainfall was applied to the pots. The rainfall was simulated according to the long term averages of the regions where the soils originated. Leaching of cations, particularly K+ and Na+ occurred only from four of the six soils when winter rainfall was simulated. In one of the sandy soils, the simulated rainfall was too low to allow leaching. In another soil, high clay content of 35% in combination with low rainfall prevented leaching. In three soils that received the same amount of rainfall, more cations leached from the duplex sandy soil compared to the two other soils. These trends indicated that leaching of cations was a function of soil texture and rainfall. The study showed that in regions with low rainfall, irrigation with winery wastewater would lead to the accumulation of cations thereby increasing soil salinity. The study confirmed that for sustainable use of winery wastewater irrigation in agriculture, different soil types will require individual management in order to avoid or minimize the negative environmental impact on natural resources by wastewater irrigation.